STATISTICAL PROCESSING OF EMPIRICAL DATA IN THE RESEARCH PROCESS - Kozimjon Kosimov; Gulnoza Karimova (PT. Antis International Publisher, 2024)
Based on preliminary analysis on the object of empirical Sociological Research, an existing problem analysis program is developed. The scientific program is the first necessary document of any practical, theoretical sociological study. The program is aimed at checking the working hypothesis on the object of sociological research, and also consists of the statements of the scientific hypothesis on research, the main tasks to be performed and the methodological basis of sociological research. This paper scientifically investigated the process of statistical processing of empirical data.